Characterization, biorecognitive activity and stability of WGA grafted lipid nanostructures for the controlled delivery of Rifampicin. (December 2015) - Pooja, Deep; Tunki, Lakshmi; Kulhari, Hitesh; Reddy, Bharathi B.; Sistla, Ramakrishna
Highlights: WGA conjugated and rifampicin loaded lipid nanoparticles were prepared by emulsification followed by solvent evaporation method. Bioconjugation of WGA was confirmed by FTIR and change in surface potential of nanoparticles. The release of RFN from the nanoparticles followed non-fickian diffusion mechanism. Haemagglutinin and mucin binding tests confirmed the retention of biorecognitive and sugar-binding specificity of WGA after conjugation. During steric stability studies, nanoparticles were stable upto 1M concentration of flocculating agent. Abstract: Targeted nanomedicines improve the delivery of drugs by increasing the drug concentration at target site, protecting the premature degradation and releasing the encapsulated drug in controlled manner. To make rifampicin (RFN) delivery more effective, we designed and characterized wheat germ agglutinin (WGA) conjugated, RFN loaded solid-lipid nanoparticles (WRSN). Nanoparticles were prepared by solvent emulsification/evaporation and conjugated with fluorescein isothiocyanate-labeled WGA. Important characteristics, such as particle size, zeta potential, encapsulation efficiency, conjugation efficiency and in vitro drug release behavior, were investigated. WGA conjugation to the nanoparticles was confirmed by Fourier Transform Infrared (FTIR) analysis. Conjugation efficiency was determined by fluorescent spectroscopy and Bradford assay. RFN was released from nanoparticles via the diffusion-controlled, non-fickian and supercase II mechanism. A haemaglutination test confirmed that WGA retained its bio-recognition activity and sugar-binding specificity after it was coupled with the nanoparticles. In vitro experiments demonstrated that WRSN interacted more than non-conjugated nanoparticles with porcine mucin. WRSN were stable in the presence of electrolytes up to 1M concentration. Therefore, WGA-conjugated solid lipid nanoparticles could be a promising tool for the controlled delivery of RFN or other anti-tubercular drugs.